Elbow medial approach open reduction and internal fixation with absorbable cannulated screws for the treatment of Kilfoyle II and III type medial condyle fractures of the humerus in children - Li, Liuyang; Li, Weiqiang; Ma, Hong; Zheng, Yugeng; Chen, Yongge; Ke, Huarong; Guo, Yueming (Frontiers in Surgery, 2025)
ObjectiveThis study aims to investigate the clinical efficacy of elbow medial approach open reduction and internal fixation with absorbable cannulated screws for the treatment of Kilfoyle II and III type medial condyle fractures of the humerus in children.MethodsA retrospective analysis was conducted on 23 pediatric patients with medial condyle fractures of the humerus who underwent surgical treatment at the Department of Pediatric Orthopedics, Foshan Traditional Chinese Medicine Hospital, from June 2018 to December 2023. Among the patients, 15 were male and 8 were female, with ages ranging from 5 to 12 years (mean age: 9.0 ± 2.4 years). According to the Kilfoyle classification, there were 3 cases of type II fractures and 20 cases of type III fractures. Of these, 19 were fresh fractures and 4 were neglected fractures. The surgical treatment involved open reduction and internal fixation through an elbow medial approach using absorbable cannulated screws. Postoperatively, the elbow joint was fixed in a functional position using a plaster cast. Four weeks postoperatively, follow-up radiographic examination showed continuous callus formation across the fracture line. The plaster cast was then removed, and active flexion and extension exercises of the elbow joint were initiated. The final follow-up assessment was performed using the Broberg-Morrey elbow joint functional scoring system to evaluate treatment efficacy.ResultsAll patients were followed up for 3–12 months. All fractures achieved bony union without any breakage of the fixation devices. Among them, 2 cases had good functional scores for the elbow joint, while the others had excellent scores. None of the patients experienced complications such as infection, vascular or nerve injury, nonunion or malunion of fractures, heterotopic ossification, avascular necrosis of the medial epicondyle, or varus/valgus deformity of the elbow joint.ConclusionOpen reduction and internal fixation through an elbow medial approach using absorbable cannulated screws demonstrates favorable clinical efficacy in treating Kilfoyle II and III type medial condyle fractures of the humerus in children. It can avoid the harm of secondary surgery to children, alleviate their pain, improve elbow joint function, and is considered the preferred method for treating pediatric medial condyle fractures of the humerus, deserving promotion and application in clinical practice.